ANALISIS TEKNIK DASAR PUKULAN DEPAN PADA PENCAK SILAT PSHT RANTING LUBUKLINGGAU BARAT 1 - Deni Pernando; Muhammad Supriyadi; Wawan Syafutra (LPPM Universitas Cipta Mandiri, 2024)
This research aims to determine the quality of basic front punch technique skills in pencak silat PSHT Ranting Lubuklinggau Barat 1. The method used in this research is a survey with a qualitative descriptive approach. The subjects of this research were pencak silat athletes consisting of 12 athletes, 4 women and 8 men. Data collection techniques used triangulation techniques through observation and interviews. The data analysis technique used to describe the research results is descriptive interview results and scores from observations. The results of data analysis in interviews with coaches and pencak silat athletes PSHT West Lubuklinggau branch 1 show: knowledge of basic front punch technique skills in pencak silat is in accordance with existing sources in theoretical studies and the results of front punch skills are very good on average; very good front punch skills. The conclusion of this research is that the average score for the front blow technique that was tested by PSHT Ranting Lubuklinggau Barat 1 pencak silat athletes is in the very good category.